Fermentation of Chicken Slaughterhouse Wastewater (CSWW) With White Sugar as A Carbon Source for Manufacturing of Liquid Fertilizer - Eduardus Budi Nursanto; Akbar Angga Handjaya; Nur Layli Amanah; Muhammad Fairuzt Fathin Faundra; Alifiana Permata Sari; Catia Angli Curie (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
Along with the increase in the production of broilers, the amount of liquid waste produced will increase. Liquid waste resulting from chicken slaughterhouse activities will cause odor pollution and aquatic pollution. Chicken slaughterhouse wastewater (CSWW) is suitable for use as a raw material for Liquid Organic Fertilizer (LOF) production, based on nutrient analysis results of waste samples collected from a facility in South Jakarta. According to the results of the analysis, the Biochemical Oxygen Demand (BOD) was measured at 214.52 mg/L, and the Chemical Oxygen Demand (COD) was significantly higher at 2310 mg/L. Furthermore, the samples contained 37.39 mg/L of oil and fat, and an ammonia (NH3) concentration of 37.39 mg/L. The presence of high concentrations of organic substances, such as protein, oil, and fat, confirms the potential of CSWW as a valuable raw material to produce LOF. To facilitate this study, bioconversion, the fermentation method was employed. In this study, four formulations of (LOF) were prepared using varied concentrations of a carbon source (sucrose) and Effective Microorganisms 4 (EM4) solution bacterial inoculum. The efficacy of these formulations was subsequently evaluated via a bioassay on land kangkong (Ipomoea reptans Poir). The results revealed that the greatest positive effect on plant growth was achieved by the LOF variation, which incorporated 150 g of sucrose and 0.05 L of EM4 solution. Samples of plants that were given the addition of LOF showed the highest number of leaves, as many as 24 strands and the highest plant height value of 18 cm.